It's summer! - Glaser, Linda; Swan, Susan 1944-. (Brookfield Conn. Millbrook Press, 2003)
A child observes the coming of summer and its effects on the weather, animals, and plants. Includes suggestions for summertime activities to enjoy alone or with a parent.
Keywords: Summer -- Fiction